Post Covid-19 Pandemic Condition: Online Consumer Purchase Intention - Fendy Cuandra (Inovbiz: Jurnal Inovasi Bisnis, 2023)
The Covid-19 pandemic that hit the world in early 2020 forced the economic sector to adapt and innovate. One of them is by switching to using an online system. This shift can be seen in many online businesses that are growing and diversifying. So this of course changes consumer buying behavior, especially online consumer purchase intentions. This study aims to conduct an in-depth analysis of the purchase intention factors of online consumers after the Covid-19 pandemic. This test is carried out by looking at whether there is an influence between social present factors, psychological distance, trust, and engagement influencing online consumer purchase intentions and the impact of mediation by engagement.Research data was obtained by distributing questionnaires to a sample of 170 online consumers in Batam City. The research data was processed and analyzed using SmartPLS 3 software. The results of data processing and analysis show that social presence, trust, and engagement affect online consumer purchase intentions. While psychological distance does not affect. Engagement does not have a mediating effect on these relationships